Do quantitative levels of antispike‐IgG antibodies aid in predicting protection from SARS‐CoV‐2 infection? Results from a longitudinal study in a police cohort - Sendi, Parham; Widmer, Nadja; Branca, Mattia; Thierstein, Marc; Büchi, Annina Elisabeth; Güntensperger, Dominik; Blum, Manuel Raphael; Baldan, Rossella; Tinguely, Caroline; Heg, Dik; Theel, Elitza S.; Berbari, Elie; et al. (Journal of medical virology, 2023)
In a COVID‐19 sero‐surveillance cohort study with predominantly healthy and vaccinated individuals, the objectives were (i) to investigate longitudinally the factors associated with the quantitative dynamics of antispike (anti‐S1) IgG antibody levels, (ii) to evaluate whether the levels were associated with protection from SARS‐CoV‐2 infection, and (iii) to assess whether the association was different in the pre‐Omicron compared with the Omicron period. The QuantiVac Euroimmun ELISA test was used to quantify anti‐S1 IgG levels. The entire study period (16 months), the 11‐month pre‐Omicron period and the cross‐sectional analysis before the Omicron surge included 3219, 2310, and 895 reactive serum samples from 949, 919, and 895 individuals, respectively. Mixed‐effect linear, mixed‐effect time‐to‐event, and logistic regression models were used to achieve the objectives. Age and time since infection or vaccination were the only factors associated with a decline of anti‐S1 IgG levels. Higher antibody levels were significantly associated with protection from SARS‐CoV‐2 infection (0.89, 95% confidence interval [CI] 0.82–0.97), and the association was higher during the time period when Omicron was predominantly circulating compared with the ones when Alpha and Delta variants were predominant (adjusted hazard ratio for interaction 0.66, 95% CI 0.53–0.84). In a prediction model, it was estimated that >8000 BAU/mL anti‐S1 IgG was required to reduce the risk of infection with Omicron variants by approximately 20%–30% for 90 days. Though, such high levels were only found in 1.9% of the samples before the Omicron surge, and they were not durable for 3 months. Anti‐S1 IgG antibody levels are statistically associated with protection from SARS‐CoV‐2 infection. However, the prediction impact of the antibody level findings on infection protection is limited.